2019
DOI: 10.1136/bjophthalmol-2018-313375
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for disease progression in low-teens normal-tension glaucoma

Abstract: Background/AimsTo investigate the risk factors for disease progression of normal-tension glaucoma (NTG) with pretreatment intraocular pressure (IOP) in the low-teens.MethodsOne-hundred and two (102) eyes of 102 patients with NTG with pretreatment IOP≤12 mm Hg who had been followed up for more than 60 months were retrospectively enrolled. Patients were divided into progressor and non-progressor groups according to visual field (VF) progression as correlated with change of optic disc or retinal nerve fibre layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 26 publications
3
32
1
Order By: Relevance
“…Interestingly, DH was not involved with the factors contributing to faster VF progression rate in this study. The presence and/or number of DH have been reported to be related to the progression of glaucoma, especially NTG [28,34]. There could be several possible interpretations of this finding.…”
Section: Plos Onementioning
confidence: 87%
See 2 more Smart Citations
“…Interestingly, DH was not involved with the factors contributing to faster VF progression rate in this study. The presence and/or number of DH have been reported to be related to the progression of glaucoma, especially NTG [28,34]. There could be several possible interpretations of this finding.…”
Section: Plos Onementioning
confidence: 87%
“…Few studies have assessed the risk factors for NTG progression in patients with well-controlled low-teen IOP. Recently, progression was reported in about 35% of the eyes of patients with low-teen NTG in more than 5 years [28]. Fluctuation of diastolic BP and diurnal IOP were suggested as systemic factors associated with progression risk in NTG patients with low-teen IOP [28].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the diurnal fluctuation in IOP may decrease from 8.6 to 4.9 mmHg, and this effect is more pronounced in phakic eyes [17]. This observation is particularly relevant to 'low-teens normal-tension' type of glaucoma, because a high degree of long-term diurnal IOP fluctuation is a significant risk factor in the progression of glaucoma [18]. In our case, IOP fluctuated by approximately 8 mmHg in the three years prior to TLE, which was reduced to approximately 2 mmHg after TLE.…”
Section: Discussionmentioning
confidence: 99%
“…A Japanese study group recently reported that the probability of NTG patients progressing to unilateral blindness was 9.9% at 20 years [12], which suggests that the NTG prognosis would be more severe than expected from the CNTGS. Additionally, individual factors that increase the risk of progression in NTG patients, such as optic disc hemorrhage [4,13], migraine [4], female [4], or IOP fluctuation [14,15], can affect the decision of Korean glaucoma subspecialists on whether to start treatment in the real-world clinical setting.…”
Section: Discussionmentioning
confidence: 99%